Effects of Inclusion Levels of Discarded Corn Grain on Growth Performance, Edible Portions and Economic Response in Broilers - Elvir, Elmer Modesto; Vega, Andrés Sebastian; Martínez, Yordan; Valdivié, Manuel; Rodríguez, Roman (International Journal of Poultry Science, 2020)
Background and Objective: The challenge for nutritionists is to formulate diets with available alternative sources to reduce production costs, without depressing animal performance. The objective of this study was to evaluate the effects of inclusion levels of discarded corn grain on growth performance, edible portions and economic response in broilers. Materials and Methods: A total of 1,200 one-day-old Ross 308® broilers were distributed in a completely randomized design with four treatments and six replications. Diets with inclusion levels of 0, 100, 200 and 300 g kg–1 of discarded corn grain were formulated. Results: Throughout the experimental stage, the inclusion level of 300 g kg–1 of discarded corn grain improved body weight and feed conversion ratio (starter and grower), without affecting feed intake (except 0-32 days). Likewise, this inclusion level (300 g kg–1) improved the viability in the grower phase compared to the control. Dietary use of discarded corn grain did not change (p